2022
DOI: 10.1111/jocd.15094
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and integrative remedies in the treatment of chronic pruritus: A review of clinical trials

Abstract: Background: Chronic pruritus is one of the most common conditions in dermatology and a common manifestation in many systemic diseases. Since the etiology of chronic pruritus remains somewhat unknown, hence, conventional medications may not always show a good therapeutic response. This finding has led both investigators and patients to use herbal and complementary remedies for its treatment. The aim of this study was to review clinical trials in which herbal and complementary medicine was used in the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…[12][13][14][15][17][18][19][20] On the other hand, studies on chronic disease management applying the integrative medicine (IM) perspective tend to be actively conducted in countries with experience in using medicinal herbs. [21][22][23][24][25][26][27][28] IM is a holistic approach that simultaneously utilizes all available complementary treatments and conventional treatments. [29] The combination of CMs and herbal remedies, in particular, as a subsection of IM, has demonstrated better therapeutic performance and safety than conventional treatments in various conditions, including coronavirus disease 2019, cancer, stroke, chronic pruritus, and rheumatoid arthritis.…”
Section: Prospero Registration Number: Crd42022296852mentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][17][18][19][20] On the other hand, studies on chronic disease management applying the integrative medicine (IM) perspective tend to be actively conducted in countries with experience in using medicinal herbs. [21][22][23][24][25][26][27][28] IM is a holistic approach that simultaneously utilizes all available complementary treatments and conventional treatments. [29] The combination of CMs and herbal remedies, in particular, as a subsection of IM, has demonstrated better therapeutic performance and safety than conventional treatments in various conditions, including coronavirus disease 2019, cancer, stroke, chronic pruritus, and rheumatoid arthritis.…”
Section: Prospero Registration Number: Crd42022296852mentioning
confidence: 99%
“…[29] The combination of CMs and herbal remedies, in particular, as a subsection of IM, has demonstrated better therapeutic performance and safety than conventional treatments in various conditions, including coronavirus disease 2019, cancer, stroke, chronic pruritus, and rheumatoid arthritis. [21,25,[30][31][32][33][34] Based on several previous studies related to this topic, it can be hypothesized that IM potentially improves the psoriasis area and severity index (PASI) and clinical symptoms and reduce AEs associated with CMs in patients with psoriasis. [35][36][37][38][39] Based on previous study knowledge and awareness, the authors set the following research objectives: Through a systematic review of randomized controlled clinical trials (RCTs), it was confirmed whether IM using EAHM is worth exploring as a useful candidate for inflammatory skin lesions in psoriasis vulgaris, thereby providing information to assist decision-making, and; Additional data analysis of the herbal prescription data collected through this review will lead to hypotheses related to promising candidates for optimal IM for psoriasis vulgaris.…”
Section: Prospero Registration Number: Crd42022296852mentioning
confidence: 99%
See 1 more Smart Citation
“…EAHM is significantly different from natural resources in other parts of the world as many similar medicinal plants are commonly listed in the pharmacopeia of East Asian countries [ 24 , 32 , 35 ]. At the same time, integrative medicine (IM) studies of chronic disease management are often conducted in countries with a history of medicinal herb use [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. IM is a comprehensive strategy that uses both complementary and conventional therapies simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…IM is a comprehensive strategy that uses both complementary and conventional therapies simultaneously. As a subset of IM, the combination of CMs and natural products has shown superior therapeutic efficacy and safety compared to standard therapies for a number of ailments, including COVID-19, cancer, stroke, chronic pruritus, and rheumatoid arthritis [ 36 , 40 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Meanwhile, a recent study using a bioinformatics approach reported that the effectiveness of widely used EAHM prescriptions in psoriasis is related to the suppression of oxidative stress and the alleviation of the resulting inflammatory pathology [ 55 ].…”
Section: Introductionmentioning
confidence: 99%